GLOBALIZATION AND INFLUENCE OF EXOGENOUS FACTORSON THE WELFARE OF THE POPULATION OF GEORGIA (Globalization and Business, 2018)
Involvement in the world economy makes the economy of Georgia and the welfare of its population more dependent on the global process and the global market conjuncture. The small size of our country’s economy, much greater import than export and consumer market satiety with imported products increases the risk of dependence on exogenous factors. The high level of dollarization of economy, savings and credit resourses strengthens the vulnerability of the welfare of Georgian economy and its population toward global processes.Today, more than 70% of consumer market comes to imported goods. In addition, Georgia, comparing to its neighbouring countries, is far behind by the negative balance of trade. In Georgia the number of wage earners out of 1000 people is twice less than in the United States of America, and the purchasing power of average salary is 6 times less than the level of the USA and 2 times less, than average global levelThe population of Georgia has decreased by 32% compared to late 1980s, while the number of employees by 1.5 times, among them employed employees - by 2.9 times.The number of migrant workers is more than 1 million and most of the mare engaged with the informal and illegal labor activities. Georgia belongs to the list of rare countries (if not the only), that has more employed citizens abroad than in its own country. Taking this into consideration the real level of unemployment in Georgia is not 13.9% as declared but about 43%.Money transfers from abroad increase the income and welfare of Georgian households by 1.3 times.Large scale involvement in the world economy has not resulted in an adequate change of cost of living and its approach to poverty level. Today, the ratio of Georgia to the USA by the price of Big Mac is 64%, by the consumer prices 39%, by the living cost – only 6.1%.